Designing Effective Carbon Border Adjustment with Minimal Information Requirements. Theory and Empirics - Alessia Campolmi; Harald Fadinger; Chiara Forlati; Sabine Stillger; Ulrich J. Wagner (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2024)
High carbon prices in the EU might drive emission-intensive industrial processes towards countries with relatively lower carbon prices. To prevent such carbon leakage, the EU's Carbon Border Adjustment Mechanism (CBAM) taxes emissions embedded in imports for the difference between carbon prices in the EU and the origin country. Because embedded emissions are very difficult to measure, CBAM applies to only five industries and accepts benchmarks instead of actual embedded emissions. These simplifications make CBAM tractable but compromise its effect on carbon leakage. We propose an alternative policy that requires no knowledge of embedded emissions and can be applied to all tradable sectors: the Leakage Border Adjustment Mechanism (LBAM). LBAM implements import tariffs (and, possibly, export subsidies) that sterilize the changes in imports (and exports) induced by a higher EU carbon price. LBAM requires information only about domestic output-to-emissions elasticities as well as elasticities of import demand and export supply, which we estimate using publicly available data. We calibrate a granular structural trade model with 57 countries and 131 sectors to quantify the welfare and emission impacts of LBAM. We find that LBAM improves over CBAM in terms of global emissions and EU welfare. We assess how 'climate clubs' of countries that adopt common carbon prices and border adjustments mechanisms perform on these outcomes.
Keywords: 330